Upaya Menghadapi Kejahatan Terhadap Sistem Keamanan Perbankan Indonesia Di Era Cyberspace - Sari, Clara Mega Kharisma; Zulfiani, Anita; Suharto, Suharto; Muhyidin, Muhyidin (Faculty of Law, Diponegoro University, 2024)
In this Cyberspace Era, the system of life in society, both Indonesian and world, has changed a lot, this can have a complete impact on people's lives, both in the form of positive and negative impacts. Along with the development of the cyber world, this is directly proportional to crime in the banking sector, these crimes are related to the banking security system. There are many crimes against the banking security system including carding crimes